Sensitive Detection of Foodborne E. coli O157:H7 by Dendrimer-aptamer Modified Microchannels - with RCA Signal Intensifications - Jiang, Yuqian (Université d'Ottawa / University of Ottawa, 2018)
Foodborne pathogenic bacterial infection is one of the main causes for food poisoning cases. Therefore there is an urgent need for rapid, sensitive and cost-effective detection methods in order to avoid or to respond to outbreaks of such diseases in a timely manner. To this end, a dendrimer-aptamer modified microfluidic detection system with rolling circle amplification (RCA) is developed to detect E. coli O157:H7. In the proposed detection system, poly(amidoamine (PAMAM) dendrimers are immobilized onto inner surfaces of polydimethyl siloxane (PDMS) microchannels to avoid non-specific binding and to provide more binding sites to subsequently conjugate capturing aptamers as recognition elements. Surface modifications by the PAMAM dendrimers and the aptamers are characterized. To further enhance detection sensitivity, RCA is employed to intensify fluorescence signals for detection. To better understand the RCA process and optimize its reaction conditions, the RCA reaction processes are followed over time using atomic force microscopy and agarose gel electrophoresis. Subsequently, the optimized RCA reaction conditions are used in a dendrimer-aptamer microfluidic whole-cell detection system for E. coli O157:H7 detection with signal RCA (sRCA) signal intensifications. To further improve the detection sensitivity, a new set of RCA sequences for capturing target bacterial cells (i.e. cRCA) are designed to produce tandem repeat aptamer units (i.e. cRCA-aptamers) for more efficient target captures. In situ cRCA synthesis on microchannel inner surface is characterized and optimized for its application in capturing E. coli O157:H7 cells. The cRCA approach shows better capturing ability and further increased the fluorescence detection signals. Our results suggest that the proposed platform is a promising method for sensitive and rapid detection of pathogenic bacterial cells.
Keywords: Food safety; Bacteria detection; Microfluidic devices; Signal amplification; Biosensor; Lab on a chip; Single-cell detection; Atomic force microscopy; Dendrimer; Aptamer